College students' sense of belonging : a key to educational success for all students - Strayhorn, Terrell L. (London : Routledge, 2012)
'Belonging with peers, in the classroom, or on campus is a crucial part of the college experience. It can affect a student's degree of academic achievement, or even whether they stay in school. Although much is known about the causes and impact of sense of belonging in students, little is known about how belonging differs based on students' social identities, such as race, gender, or sexual orientation, or the conditions they encounter on campus. College Students' Sense of Belonging addresses these student sub-populations and campus environments. It offers readers practical guidelines, underpinned by theory and research, for helping students belong and thrive. Sense of belonging can come from peers, teachers or faculty, family members, social and academic groups, and living and learning environments. The book offers: a review and critique of current literature on sense of belonging in light of new and emerging theory a new conceptual model of belonging which helps the reader expand an understanding of sense of belonging new and recent research findings from quantitative, qualitative, and mixed methods studies conducted by the author practical recommendations for improving educational environments, practices, policies, and programs to facilitate students' sense of belonging on campus.'-- Provided by publisher.
Includes bibliographical references (p. [127]-137) and index.
Keywords: College students -- United States -- Psychology; Minority college students -- United States -- Psychology; Student adjustment -- United States; College environment -- United States; Belonging (Social psychology)